2016
DOI: 10.1063/1.4966144
|View full text |Cite
|
Sign up to set email alerts
|

Robust shell passivation of CdSe colloidal quantum dots to stabilize radioluminescence emission

Abstract: Systematic characterization of semiconductor colloidal quantum dots (cQDs) response to ionizing radiation must be performed to use them in radiation detection. In this study, the robustness of multi-shell (MS) and core/shell (CS) cQDs was investigated under irradiation. Radioluminescence (RL) measurements with kV and MV photon beams revealed a better resistance of MS cQDs to ionizing radiation, with their spectra fluctuating by barely ∼ 1 nm. A systematic signal recovery between subsequent irradiations was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, embedding of Q-dots of direct gap semiconductors into a suitable transparent host can give rise to bulk scintillators with limited reabsorption and superfast scintillation response [124]. Note that radiation hardness has been improved using core-shell architectures [128]. Out of the scintillation field, it has been demonstrated that bulky materials, such as aerogel, superlatices, and even mixture of QDs and lead based-perovskite, can be prepared [129]- [131].…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Furthermore, embedding of Q-dots of direct gap semiconductors into a suitable transparent host can give rise to bulk scintillators with limited reabsorption and superfast scintillation response [124]. Note that radiation hardness has been improved using core-shell architectures [128]. Out of the scintillation field, it has been demonstrated that bulky materials, such as aerogel, superlatices, and even mixture of QDs and lead based-perovskite, can be prepared [129]- [131].…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The cQD concentration of the solutions was approximately 22 µm. A detailed description of the cQD synthetic methods and dispersion in solvents can be found elsewhere (Lecavalier et al 2013, Delage et al 2016. Two types of dosimeter were tested: a plastic optical fiber, Eska GH-4001 (Industrial Fiber Optics, Tempe, USA) coupled to the cQD powder, as has been described previously (Delage et al 2016) and the other was the cQD liquid dispersions contained in glass recipients.…”
Section: Cqd-based Dosimeters Descriptionmentioning
confidence: 99%
“…This linearity holds over a clinically relevant dose range representative of an intra-fraction external beam therapy measurement (EBRT) (∼2 Gy). Furthermore, the dosimeters have previously shown potential for keeping this signal proportionality over higher dose values without saturation in light signal (Delage et al 2016).…”
Section: Linearity Of the Scintillation Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…One could argue that historically the first quantum-confining nanocrystals were made by melting both glass and semiconductor precursors at high temperature, nucleating quantum dots throughout the glass structure, and hence naturally yielding preforms for the first category of nanocomposite optical fibers. This glass melt-quenching method does not allow for elaborate control of the nanocrystal surface passivation, , thus defects degrade the PL emission, creating further challenges to control the density of nanocrystals and their size distribution. A second category of debatably nanocomposite fibers thus recently emerged: doping optical fibers with cQDs using a number of postprocessing techniques, such as filling hollow core fibers with a liquid containing cQDs and coating the core of microstructured optical fibers or fiber tapers and ends. These techniques seem a priori advantageous in their chemical simplicity and flexibility, benefiting from the separate synthesis of cQDs under well controlled conditions enabling passivation with heterostructures of multiple semiconductor shells , and even with further surface ligand exchange afterward. ,, However, the lack of stability and robustness coupled with high optical losses in the cQD host solvents limits the practicality of liquid core fibers, with the added drawback of air exposure when the solvent evaporates, causing surface chemical reactions that increase photobleaching and photoactivation.…”
Section: Introductionmentioning
confidence: 99%